Institute for evaluating judges as an element of the state judicial system - Бакаянова, Нана Мезенівна; Бакаянова, Н. М.; Бакаянова, Нана Мезеновна; Bakaianova, Nana M.; Артеменко, Ігор Анатолійович; Артеменко, І. А.; Артеменко, Игорь Анатольевич; Artemenko, Ihor A.; Пушкар, Сергій Іванович; Пушкар, С. І.; Пушкарь, Сергей Иванович; Pushkar, Serhii I.; et al. (Allied Business Academies, 2020)
The article is devoted to the study of the specifics of the institute for evaluating as an element of the state judicial system. It is clarified the purpose of evaluating judges and the importance of the institute for maintaining the image of the judicial authorities in the state as a whole. It is established that states are cautiously concerned about the institution for evaluating judges in view of the contradiction and to the judges’ independence principle, so the main task of each state that introduces such an institution is to ensure a balance between the legal goals of evaluating judges and observing the principle of judges’ independence. It is determined that another essential condition for evaluating judges is the availability of objective, clear and transparent evaluation criteria. There are considered the criteria for evaluating judges in Italy, the Netherlands and Ukraine. It is noted that it is important to develop a standard for evaluating judges in the European Union states, which would make it possible to eliminate the disparate treatment of judges in different states. There are highlighted the directions of improving the evaluation of judges in Ukraine, namely, fixing transparent procedures for checking the results of judges’ evaluation and attracting citizens to evaluate judges on a paid basis.

Стаття присвячена дослідженню специфіки інституту оцінювання як елемента державної судової системи. З'ясовано призначення оцінки суддів та значення інституту для підтримки іміджу судової влади в державі в цілому. Встановлено, що держави обережно ставляться до інституту оцінювання суддів з огляду на суперечність і принцип незалежності суддів, тому основним завданням кожної держави, яка запроваджує такий інститут, є забезпечення балансу між правовими цілями оцінювання суддів та дотриманням принципу незалежності суддів. Визначено, що ще однією важливою умовою оцінювання суддів є наявність об’єктивних, чітких та прозорих критеріїв оцінювання. Розглянуто критерії оцінювання суддів в Італії, Нідерландах та Україні. Зазначається, що важливо розробити стандарт оцінювання суддів у країнах Європейського Союзу, який дозволив би усунути різне ставлення до суддів у різних державах. Висвітлено напрямки вдосконалення оцінювання суддів в Україні, а саме закріплення прозорих процедур перевірки результатів оцінювання суддів та залучення громадян до оцінювання суддів на платній основі.
Artemenko I. Institute for evaluating judges as an element of the state judicial system / I. Artemenko, N. Bakaianova, S. Pushkar, S. Naumenko, A. Kubaienko // Journal of Legal, Ethical and Regulatory Issues. - Vol. 23. - Issue 5. - Allied Business Academies, 2020. – P. 1–6.
Keywords: judicial system; judicial authorities; judges; judges’ evaluation; judges’ independence; evaluation criteria; competence; virtue; professional ethics; судова система; органи юстиції; судді; оцінка суддів; незалежність суддів; критерії оцінки; компетентність; чеснота; професійна етика; Research Subject Categories::LAW/JURISPRUDENCE